A public survey on knowledge, awareness, attitude and willingness to pay for WEEE management: Case study in Bangladesh. (20th November 2016) - Islam, Md. Tasbirul; Abdullah, A.B.; Shahir, S.A.; Kalam, M.A.; Masjuki, H.H.; Shumon, Rezaul; Rashid, Md. Humayun
Abstract: This article is a first, limited attempt made to understand public knowledge, awareness, attitude and willingness to pay (WTP) in WEEE management in the context of Bangladesh, with a particular focus on the level of awareness, knowledge on WEEE, the reasons of discarding, priority choice, and disposal method. The purpose of this paper is to provide scientific knowledge basis promoting a policy agenda by assessing current WEEE management trend among households. Survey data has been collected by distributing questionnaires randomly in 7 residential areas in Dhaka, and interviewing 400 households. This study found a very limited knowledge on WEEE among households (i.e. only 9%). Competitive price, warranty period, brands and installment facilities are found important economic factors during the new purchase of electronic products. The actual life cycle of mobile phone, personal computers and television sets varies from 2 to 6 years. With the presence of informal sector WEEE collection and recycling, this study found that 30% of the households were selling WEEE items to scrap collectors for economic benefits. More than 20% of the respondents have thrown WEEE with household waste. Only 5–10% of the respondents are willing to pay for any new WEEE management system. Enacting effective regulations, developing national WEEE inventory database, environmental awareness building through education and stakeholders participation in creating economic value chain; are suggested through this study. This research is one of a kind in investigating the attitudes of the households of a developing nation towards WEEE management and will show the pattern of WEEE generation, disposal and management practice in the most densely populated city in the world, i.e., Dhaka, Bangladesh. Results found from this research are expected to create a primary basis for encouraging scientific discussion and understanding the situation at policy level in Bangladesh and will also pave the way for a successful WEEE management policy making in any similar social and economic conditions. Highlights: Current status of WEEE management in Bangladesh is investigated. Public perception on WEEE management is discussed. Policy implications are described to promote WEEE management more effectively in Bangladesh. 68% of the households found to have no familiarity with WEEE management. Future research directions for academics and policy makers are highlighted.